KNOWLEDGE AND ATTITUDES ABOUT ADVANCE CARE PLANNING AMONGST AN OLDER ADULT POPULATION LIVING IN SOUTH EAST QUEENSLAND. Issue 2 (1st June 2013) - Crowe, L; Boddy, J; Chenoweth, L
Abstract : Background: The introduction of Advance Care Planning (ACP) in the hospital context when people are 'vulnerable and unwell' is challenging. The 'Creating pathways to advance care planning: empowering the health consumer' research and education project explored the knowledge base of people aged 60 years and over living in the community. Current knowledge on ACP and associated terms and legislation prior and post to a community education programme were investigated. Aim: To understand and improve the knowledge and attitudes of people over the age of 60 years to ACP in South East Queensland. Methods: Employing intervention and control groups n=150 people participated in community education. Both groups completed a pre-questionnaire to ascertain their knowledge base on ACP. Participants then engaged in an interactive training programme on ACP. Post questionnaires were completed following the education and 4–6 months after the training. Results: While the majority of participants were familiar with terms related to ACP most were not able to articulate what the terms meant. Participants were confused by the paperwork with many hoping their relatives or doctors would 'work it out for them'. Participants found the education empowering with many engaging in formal and informal ACP following the workshops. Discussion: Despite growing awareness of ACP, medical terminology and legislative requirements continue to be misunderstood. Although wanting to remain independent, participants perceived that there were too many barriers to engaging in ACP prior to engagement in the training. Conclusion: ACP continues to be confusing and overwhelming to people over the age of 60 years living in the community and there is a significant role for community education.